Quality of Birth Certificate Issuance Services in Kapuas Murung District, Kapuas Regency - Muliadi, Muliadi; Azkar, Nurul (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the quality of birth certificate services in Kapuas Murung District, Kapuas Regency. Through a qualitative approach, it can be described that the quality of birth certificate services in Kapuas Murung District is still low because it is unable to complete three working days, thus triggering public dissatisfaction. This is due to limited human resources (apparatus) and limited service facilities in the form of computers, unstable internet networks, and frequent power outages at the Kapuas Murung District office. In addition, the long distance between several villages and the Kapuas Murung District office with inadequate road conditions adds to the burden on the community in accessing birth certificate services. Therefore, it is recommended that the Kapuas Murung District government add apparatus and supporting service facilities.